Work-Life Balance, Job Stress, and Turnover: The Pivotal Role of Job Satisfaction (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study investigates the determinants of turnover intention among millennial employees, examining the direct and mediated roles of work-life balance, job stress, and job satisfaction. Data were collected from 180 millennial workers using a saturated sampling technique and analyzed with PLS-SEM. The findings reveal a nuanced model: job stress directly increases turnover intention, whereas work-life balance has no direct effect. Interestingly, both work-life balance and job stress significantly enhance job satisfaction. However, job satisfaction itself does not translate into reduced turnover intention. Consequently, job satisfaction fails to function as a significant mediator. These results challenge conventional models, underscoring the primacy of direct stress management over enhancing job satisfaction as a strategy to mitigate turnover intention in this demographic.
Keywords: work-life balance; job stress; job satisfaction; turnover intention